The Dark Energy Survey Supernova Program results: type Ia supernova brightness correlates with host galaxy dust. Issue 2 (26th October 2022) - Meldorf, C; Palmese, A; Brout, D; Chen, R; Scolnic, D; Kelsey, L; Galbany, L; Hartley, W G; Davis, T M; Drlica-Wagner, A; Vincenzi, M; Annis, J; et al.
ABSTRACT: Cosmological analyses with type Ia supernovae (SNe Ia) often assume a single empirical relation between colour and luminosity (β) and do not account for varying host-galaxy dust properties. However, from studies of dust in large samples of galaxies, it is known that dust attenuation can vary significantly. Here, we take advantage of state-of-the-art modelling of galaxy properties to characterize dust parameters (dust attenuation AV, and a parameter describing the dust law slope RV ) for 1100 Dark Energy Survey (DES) SN host galaxies. Utilizing optical and infrared data of the hosts alone, we find three key aspects of host dust that impact SN cosmology: (1) there exists a large range (∼1–6) of host RV ; (2) high-stellar mass hosts have RV on average ∼0.7 lower than that of low-mass hosts; (3) for a subsample of 81 spectroscopically classified SNe there is a significant (>3σ) correlation between the Hubble diagram residuals of red SNe Ia and the host RV that when corrected for reduces scatter by 13 per cent and the significance of the 'mass step' to ∼1σ. These represent independent confirmations of recent predictions based on dust that attempted to explain the puzzling 'mass step' and intrinsic scatter (σint ) in SN Ia analyses.